Senior Managers' Viewpoints Toward Challenges of Implementing Clinical Governance: A National Study in Iran - Hamid Ravaghi; Peigham Heidarpoor; Maryam Mohseni; Sima Rafiei (Kerman University of Medical Sciences, 2013)
BackgroundQuality improvement should be assigned as the main mission for healthcare providers. Clinical Governance (CG) is used not only as a strategy focusing on responding to public and government's intolerance of poor healthcare standards, but also it is implemented for quality improvement in a number of countries. This study aims to identify the key contributing factors in the implementation process of CG from the viewpoints of senior managers in curative deputies of Medical Universities in Iran. MethodsA quantitative method was applied via a questionnaire distributed to 43 senior managers in curative deputies of Iran Universities of Medical Sciences. Data were analyzed using SPSS. ResultsAnalysis revealed that a number of items were important in the successful implementation of CG from the senior managers' viewpoints. These items included: knowledge and attitude toward CG, supportive culture, effective communication, teamwork, organizational commitment, and the support given by top managers. Medical staff engagement in CG implementation process, presence of an official position for CG officers, adequate resources, and legal challenges were also regarded as important factors in the implementation process. ConclusionKnowledge about CG, organizational culture, managerial support, ability to communicate goals and strategies, and the presence of effective structures to support CG, were all related to senior managers' attitude toward CG and ultimately affected the success of quality improvement activities.